Juvenile nasopharyngeal angiofibroma: National practice patterns and resource utilization via HCUP KID. (October 2021) - Pool, Christopher; Gates, Christopher J.; Patel, Vijay A.; Carr, Michele M.
Abstract: Background: Juvenile nasopharyngeal angiofibroma (JNA) is a locally aggressive benign vascular tumor that typically afflicts young adolescent males. Historically removed via open approaches, these tumors are now being removed endoscopically. As the modern healthcare setting emphasizes value, efficient utilization of resources may lead to decreased cost while maintaining or improving patient outcomes. Objective: The objective of this study was to investigate how perioperative management of juvenile nasopharyngeal angiofibromas (JNAs) influence overall cost. We specifically investigate the effect of approach type (open, endoscopic, or combined) with regards to cost and length of stay. We also delineated practice patterns, analyzed safety profiles, and characterize clinical outcomes. Methods: The 2016 Healthcare Cost and Utilization Project Kids' Inpatient Database (HCUP-KID) was queried to identify males aged <21 years with an ICD-10-CM diagnosis code of D10.6 (benign neoplasm of nasopharynx) and ICD-10-PCS codes to determine whether an open, endoscopic or combined approach was performed. Univariate statistical analysis and multivariable logistic regression were performed to examine the effects of demographics, patient characteristics, procedure type, and complications on length of stay (LOS) and cost. Results: A total of 89 male patients were analyzed with a mean age of 14.8 years (range 8–20 years). Mean LOS was 3.4 days. Mean total charges were $128, 780. Comparing open (n = 16), endoscopic (n = 65), and combined (n = 8) approaches, there was a significant difference in the need for fresh frozen plasma (p = 0.02) and packed red blood cell (pRBC) (p = 0.03) transfusion but no difference in preoperative embolization (p > 0.05) between approach types. LOS was associated with age (p = 0.02), pRBC transfusion (p = 0.04) and septal deviation (p = 0.03). Charges varied with LOS (p < 0.001) on linear regression analysis but not with other variables in this dataset. Conclusion: Approach type for JNA appears to be unrelated to LOS or charges in this multi-site, population-based analysis. However, septal deviation, pRBC transfusion, and young age are associated with increased LOS in patients undergoing JNA resection.